Implementasi strategi pembelajaran critical incident pada pembelajaran nilai pancasila - Maulinawati, Yusriana; Wahyuningsih, Siti; Suharno, Suharno (Universitas Sebelas Maret, 2021)
This study was conducted to describe the implementation of the Critical Incident strategy in learning Pancasila values which was carried out online during the pandemic. The method used in this research is descriptive qualitative with a case study approach. The subjects to be studied are teachers and students of class V SD Munggung II for the 2020/2021 academic year. The research subject was taken using purposive sampling technique. The data source of this research is the process of implementing the critical incident strategy, teachers, and students of class V SD Munggung II. Data collection techniques were carried out by interviews, observations, and questionaires. Data validation uses source triangulation and technique triangulation. Data analysis was carried out using Miles and Huberman through data reduiction techniques, data presentation, and data verification. Results the research shows that the implementation of the critical incident strategy in learning Pancasila Values that is carried out online only some students take part in Pancasila Values learning because conditons and situations require learning to be carried out online, the teacher’s lack of understanding of strategies, models, and learning methods, ineffective scenario preparation, constrained by signals and the economic limitations of students families who can only have one gadget.